Analisis Bahan Ajar Matematika Materi Perkalian Bilangan Cacah pada Kurikulum Merdeka Kelas IV SD - Susilawati, Lilis; Apriani, Ika Fitri; Suryana, Yusuf (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This research was motivated by curriculum changes in the world of education which caused updates in the teaching materials used in the learning process, especially in mathematics subjects multiplication material for numbers. This research aims to analyze Mathematics teaching materials for multiplication of numbers in the kurikulum merdeka of grade IV Elementary School. This research method is a qualitative descriptive research method. Research data were collected by interview, observation and documentation study techniques. The subjects in this study were class teachers located in Ciamis Regency, namely grade IV teachers of SDN 2 Sumberjaya and SDN 2 Cihaurbeuti and class teachers located in Tasikmalaya City, namely grade IV teachers of SDN 2 Tuguraja. The implications of this study show that the mathematics teaching materials for the multiplication of numbers in grade IV have met the curriculum standards, but there are still obstacles that need to be overcome. These findings can be the basis for developers to design more comprehensive teaching materials, so that they can improve students' understanding. Thus, the development of teaching materials that are more complete and in accordance with the needs of students is expected to support a more effective learning process in the independent curriculum. Keywords: Teaching materials; multiplication of small numbers; independent curriculum.